A putative xanthine dehydrogenase is critical for Borrelia burgdorferi survival in ticks and mice. Issue 1 (25th January 2023) - Phelan, James P.; Bourgeois, Jeffrey S.; McCarthy, Julie E.; Hu, Linden T.
Abstract : Borrelia burgdorferi is a pathogenic bacterium and the causative agent of Lyme disease. It is exposed to reactive oxygen species (ROS) in both the vertebrate and tick hosts. While some mechanisms by which B. burgdorferi ameliorates the effects of ROS exposure have been studied, there are likely other unknown mechanisms of ROS neutralization that contribute to virulence. Here, we follow up on a three gene cluster of unknown function, bb_0554, bb_0555, and bb_0556, that our prior unbiased transposon insertional sequencing studies implicated in both ROS survival and survival in Ixodes scapularis . We confirmed these findings through genetic knockout and provide evidence that these genes are co-transcribed as an operon to produce a xanthine dehydrogenase. In agreement with these results, we found that B. burgdorferi exposure to either uric acid (a product of xanthine dehydrogenase) or allopurinol (an inhibitor of xanthine dehydrogenase) could modulate sensitivity to ROS in a bb_0554-bb_0556 dependent manner. Together, this study identifies a previously uncharacterized three gene operon in B. burgdorferi as encoding a putative xanthine dehydrogenase critical for virulence. We propose renaming this locus xdhACB .